Early pleural fluid dynamics following video-assisted thoracoscopic lobectomy has limited clinical value - Holbek, Bo Laksáfoss; Petersen, René Horsleben; Kehlet, Henrik; Hansen, Henrik Jessen (Journal of Thoracic Disease, 2017)
The objective of this study was to evaluate the potential of predicting the pleural fluid output in patients after video-assisted thoracoscopic lobectomy of the lung. Detailed measurements of continuous fluid output were obtained prospectively using an electronic thoracic drainage device (Thopaz+™, Medela AG, Switzerland). Patients were divided into high (≥500 mL) and low (